Triantennary GalNAc Molecular Imaging Probes for Monitoring Hepatocyte Function in a Rat Model of Nonalcoholic Steatohepatitis. Issue 24 (9th November 2020) - Mishra, Anurag; Castañeda, Tamara R.; Bader, Erik; Elshorst, Bettina; Cummings, Sheila; Scherer, Petra; Bangari, Dinesh S.; Loewe, Claudia; Schreuder, Herman; Pöverlein, Christoph; Helms, Mike; Jones, Seth; et al.
Abstract: Nonalcoholic steatohepatitis (NASH) is a progressive form of nonalcoholic fatty liver disease that can lead to irreversible liver cirrhosis and cancer. Early diagnosis of NASH is vital to detect disease before it becomes life‐threatening, yet noninvasively differentiating NASH from simple steatosis is challenging. Herein, bifunctional probes have been developed that target the hepatocyte‐specific asialoglycoprotein receptor (ASGPR), the expression of which decreases during NASH progression. The results show that the probes allow longitudinal, noninvasive monitoring of ASGPR levels by positron emission tomography in the newly developed rat model of NASH. The probes open new possibilities for research into early diagnosis of NASH and development of drugs to slow or reverse its progression. Abstract : New multifunctional positron emission tomography (PET) probes are shown that target the hepatocyte‐specific asialoglycoprotein receptor, the expression of which decreases during nonalcoholic steatohepatitis progression. The probes allow longitudinal, noninvasive monitoring of receptor levels by PET in the newly developed rat model allowing to study the progress of nonalcoholic steatohepatitis progression without biopsy.